Ion beam irradiation of phase change materials: A route to material properties investigation and engineering. (15th November 2021) - Privitera, S.M.S.; Rimini, E.
Abstract: In this paper we review the effects of ion beam irradiation on phase change materials. We report and discuss the results of experiments with light, medium and heavy ions, with energies in the range of 10–200 keV. Light ions, from carbon to fluorine, have been adopted as dopants, with the purpose to increase the crystallization temperature, without inducing structural or electronic modifications. Argon, as a medium-light ion, has been employed to produce diluted cascades and therefore for studying the disordering process without melting and quenching, identifying the electronic and structural transitions occurring as the disorder increases from the stable crystalline phase up to complete amorphization. Heavy ions, including Ge, Sb and Bi, have been shown to be a suitable choice to obtain large amorphous areas with properties very similar to the melt-quenched amorphous, as formed in a phase change memory cell. Like melt-quenched regions, phase change films irradiated with heavy ions usually exhibits lower crystallization time, which can be tuned with the ion fluence. Results on GeTe and GeSbTe alloys are compared. The mechanisms producing the main observed effects are discussed, underlying the crucial role of the vacancy and of the atomic mobility.